2022
DOI: 10.1111/1440-1703.12371
|View full text |Cite
|
Sign up to set email alerts
|

Review: Monitoring of land cover changes and plant phenology by remote‐sensing in East Asia

Abstract: To achieve a sustainable society and solve the problems caused by climate change and socioeconomic activities, it is necessary to monitor the spatial and temporal variability of ecosystem functions, services, and biodiversity at both regional and global scales. During the last decade, we have seen rapid and significant improvement in satellite and near-surface remote-sensing technologies. In this review, we describe how remote-sensing observations are being used to effectively evaluate the spatial and temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 140 publications
(173 reference statements)
0
9
0
Order By: Relevance
“…Takeuchi et al (2021) emphasized the necessity of satellite observations that provide the academic perspectives and evidence needed to implement natural ecosystem conservation policies. We further encourage the use of in situ observed data to improve the accuracy and precision of analyses of satellite observations and reinforcing the networking of research communities working with in situ and satellite observations in the Asian tropics (Dronova and Taddeo, 2022;Shin et al, 2023).…”
Section: Developing Integrative Analysis and Evaluation Of In Situ An...mentioning
confidence: 89%
See 3 more Smart Citations
“…Takeuchi et al (2021) emphasized the necessity of satellite observations that provide the academic perspectives and evidence needed to implement natural ecosystem conservation policies. We further encourage the use of in situ observed data to improve the accuracy and precision of analyses of satellite observations and reinforcing the networking of research communities working with in situ and satellite observations in the Asian tropics (Dronova and Taddeo, 2022;Shin et al, 2023).…”
Section: Developing Integrative Analysis and Evaluation Of In Situ An...mentioning
confidence: 89%
“…How can we detect the characteristics of phenology in tropical rain forests consisting of evergreen broad-leaved trees, with seasonality much less clear than that of deciduous trees, with optical sensors on board satellites? Previous studies reported that the RGB composite images observed by the Sentinel-2A/2B-MSI satellites, with the highest spatial resolution among the optical sensors on board public satellites, detected the color change on the canopy surface of Castanopsis sieboldii, Castanopsis cuspidate, and Lithocarpus edulis (evergreen oak tree species) caused by leaf flush (light green) and successive flowering (cream) in Japan (Nagai et al, 2020b;Shinohara and Nasahara, 2022;Shin et al, 2023) during a general flowering in 2019. These results indicate the possibility that satellite-based observations may be used to track the phenological timing and patterns of various tree species in tropical rain forests in tandem with ground-truth information.…”
Section: Monitoring Of Plant Phenology By Using Advanced Resolution S...mentioning
confidence: 99%
See 2 more Smart Citations
“…It can detect the spatio-temporal variability of land surface changes in the landscape at a large scale (from local to regional) on a scale of seasons to decades. Recent technological developments have dramatically increased the spatial resolution and temporal frequency of satellite observations (Moon et al, 2021;Wu et al, 2021;Shin et al, 2023a;2023b;Wang et al, 2023). When a disaster occurs, detailed data on damage caused by landslides, floods, and tsunamis can be obtained with optical sensors and synthetic aperture radar (SAR) onboard satellites (Rao and Lin, 2011;Huyck et al, 2014;Boschetti et al, 2015;Miura and Nagai, 2020;.…”
Section: Introductionmentioning
confidence: 99%